Effect of Swimming Training with Hesperidin on Gene Expression Related Dopaminergic Neuron Survival in an Animal Model of Parkinson\'s Disease - Asma Taraz; Mehrzad Moghadasi; Zahra Mosalanezhad; Somayeh Rashidfard (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: Parkinson's disease (PD) is a neurodegenerative disorder characterized by the progressive loss of dopaminergic neurons in the substantia nigra. Antioxidant consumption and exercise may be important for these neurons’ survival. The current study looked at how swimming training with hesperidin affected the survival of dopaminergic neurons linked to gene expression in an animal model of Parkinson's disease. Methods: In this experimental study, 25 male Wistar rats aged 8-10 weeks were divided into five groups, including: (1) healthy control, (2) PD (3) hesperidin (4) swimming and (5) swimming + hesperidin. The rats in groups 4 and 5 participated in swimming exercises for six weeks, while the rats in groups 3 and 5 received 500 mg/kg body weight of hesperidin throughout the intervention protocol. Two days following the final intervention session the expressions of the DJ-1 and LRRK2 genes were measured using the Real-time PCR method. The data were analyzed using one-way ANOVA, and Bonferroni post hoc tests were run using SPSS Software version 16 at a significance level of P <0.05. Results: Induction of Parkinson’s disease with reserpine resulted in a notable decrease in DJ-1 gene expression, and an increase in LRRK2 gene expression (P< 0.05). The results showed that DJ-1 gene expression was appreciably elevated in the swimming, hesperidin, and swimming + hesperidin groups, while LRRK2 gene expression was significantly lower compared to the PD group (P < 0.001). The level of DJ-1expression was significantly higher in the swimming and swimming + hesperidin groups (P < 0.001), whereas LRRK2 expression was significantly reduced in these groups compared to the hesperidin-only group. Furthermore, the expression of DJ-1 in the swimming + hesperidin group was significantly higher than that observed in the swimming-only group (P < 0.001). Conclusion: By upregulating the expression of the DJ-1gene and downregulating the expression of the LRRK2 gene, swimming exercise combined with hesperidin consumption appears to be beneficial in maintaining  and surviving dopaminergic neurons in PD samples